Path Analysis of Food Literacy and eHealth Literacy on Diet Quality through Nutritional Self-Efficacy among Pregnant Women in Urban Indonesia: A Cross-Sectional Study - Lina Fitriani; Supriadi Supriadi; Rosdiana Rosdiana; Andi Misna; Rochmawati Rochmawati (Borneo Scientific Publishing, 2026)
Maternal diet quality during pregnancy remains critically suboptimal in Indonesia, contributing to the high prevalence of anemia and adverse pregnancy outcomes. This study aimed to analyze the direct and indirect effects of food literacy and eHealth literacy on diet quality through nutritional self-efficacy among pregnant women in urban Indonesia. A cross-sectional analytical study was conducted on 238 pregnant women in the second and third trimesters at Puskesmas Wara Selatan, Palopo City, South Sulawesi. Data were collected using four validated instruments: the Self-Perceived Food Literacy Scale, the eHealth Literacy Scale (comprising the core eHEALS items and a digital information access sub-dimension), the Nutrition Self-Efficacy Scale, and the Minimum Dietary Diversity for Women indicator via 24-hour dietary recall. Partial Least Squares Structural Equation Modeling with 5,000 bootstrap resamples was employed. Results showed that food literacy had the strongest direct effect on diet quality (β=0.689; p<0.001) and significantly predicted nutritional self-efficacy (β=0.453; p<0.001). eHealth literacy significantly influenced nutritional self-efficacy (β=0.484; p<0.001) but did not directly affect diet quality (β=0.162; p=0.254). Nutritional self-efficacy significantly predicted diet quality (β=0.140; p=0.036) and served as a partial mediator in the food literacy–diet quality pathway and a full mediator in the eHealth literacy–diet quality pathway. The model explained 48.5% of diet quality variance and 77.8% of nutritional self-efficacy variance. These findings confirm that nutritional self-efficacy constitutes a critical intervention point for optimizing maternal diet quality in urban primary healthcare settings.